2009
DOI: 10.2134/agronj2007.0328
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcrossing in Maize Hybrid Seed Production

Abstract: Controlling pollination of the female inbred is critical to achieve maximum kernel set and high levels of genetic purity in maize (Zea mays L.) hybrid seed production. Although kernel set associated with inbred fl owering dynamics is fairly predictable, it has not been possible to predict the level of outcrossing resulting from adventitious pollen entering the seed fi eld. Our objective was to combine our kernel set model with a new Lagrangian pollen dispersal model to determine whether outcrossing could be si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…These approaches make the reasonable assumption that the more local factors are taken into account, the more accurate the estimations at the field scale become. Recently, the biophysical approach was validated with success on individual experimental fields by Dietiker et al (2011) and Astini et al (2009) for hybrid and seed production fields, respectively. However, they are also extremely laborious to develop, due to the need to model each biological and physical process (Marceau et al, , 2012Viner et al, 2010;Chamecki et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches make the reasonable assumption that the more local factors are taken into account, the more accurate the estimations at the field scale become. Recently, the biophysical approach was validated with success on individual experimental fields by Dietiker et al (2011) and Astini et al (2009) for hybrid and seed production fields, respectively. However, they are also extremely laborious to develop, due to the need to model each biological and physical process (Marceau et al, , 2012Viner et al, 2010;Chamecki et al, 2011).…”
mentioning
confidence: 99%
“…However, they are also extremely laborious to develop, due to the need to model each biological and physical process (Marceau et al, , 2012Viner et al, 2010;Chamecki et al, 2011). Recently, the biophysical approach was validated with success on individual experimental fields by Dietiker et al (2011) and Astini et al (2009) for hybrid and seed production fields, respectively. However, because application of these models require so many site-specific parameters, it is not practical to use these models for specifying coexistence rules at the European scale.…”
mentioning
confidence: 99%
“…8), suggesting that it may be possible to develop relationships between the quantity of pollen at a given location and the likelihood of gene flow. In fact, Astini et al (2009) have shown that a simple comparison between the quantity of adventitious pollen and the quantity of locally produced pollen could reasonably predict the likelihood of gene flow within a few hundred meters of an adventitious source. Comparison of our results with Watrud et al (2004) suggests it would be worth exploring a similar approach even at greater distances.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their characteristics, maize pollen grains settle to the ground rapidly and have usually a short flight range (Jarosz et al, 2005). However, vertical wind movements or gusts during pollen shedding can lift pollen up high in the atmosphere and distribute it over significant distances up to kilometres (Jarosz et al, 2005;Astini et al, 2009;Vogler et al, 2009;Hofmann et al, 2010). However, vertical wind movements or gusts during pollen shedding can lift pollen up high in the atmosphere and distribute it over significant distances up to kilometres (Jarosz et al, 2005;Astini et al, 2009;Vogler et al, 2009;Hofmann et al, 2010).…”
Section: Plant To Plant Gene Transfer and Its Consequences 39mentioning
confidence: 99%
“…Approximately 95-99 % of the released pollen is deposited within about 50 m from the source. However, vertical wind movements or gusts during pollen shedding can lift pollen up high in the atmosphere and distribute it over significant distances up to kilometres (Jarosz et al, 2005;Astini et al, 2009;Vogler et al, 2009;Hofmann et al, 2010). Concentrations of viable pollen considerably decrease with height (Aylor et al, 2006) and distance (Jarosz et al, 2005) from the source.…”
Section: Plant To Plant Gene Transfer and Its Consequences 39mentioning
confidence: 99%